Multiple ways of perceiving and understanding the social networking sites / Dianne Cheong Lee Mei - Cheong, Dianne, Lee Mei (Centre for Media and Information Warfare Studies, 2009)
The characteristics of online communities may vary based on the quality or depth of their social relationship that members form with other individuals within the digital environment, mutual goals, and shared interests (Bagozzi & Dholakia, 2002). It is clearly recognized that community members who are active in and passionate about sharing their views on topics, products, and companies are the driving force behind the online community's value (Cothrel, 2000). Williams and Cothrel (2000) have noted that fostering personal connections among members and encouraging communication and a supportive environment as good practices in online communities. Similarly, Ridings and Gefen (2004) found information exchange and social support to be the two most popular reasons for joining an online community